1907-08 Okla. Sess. Laws 562, ch. 59, art. 1, § 1 - (:unkn) unknown (My University, 1908)
The governor of the state shall be the commander-in-chief of the militia, and as such shall have supreme command of the military forces of the state while in the service of the state, or until they are ordered and accepted into the service of the United States. While in the service of the state, he shall have power at any time to muster out any militia organization of the state, and he may discharge any enlisted man, and he may cause to be mustered out and discharged any commissioned officers who shall wilfully [sic] neglect the duties of his office, or shall fail to properly account for public property or money in his possession, as such officer.
Keywords: ARMED FORCES